What about synthetic signing? A methodology for signer involvement in the development of avatar technology with generative capacity - Dimou, Athanasia-Lida; Papavassiliou, Vassilis; Goulas, Theodoros; Vasilaki, Kyriaki; Vacalopoulou, Anna; Fotinea, Stavroula-Evita; Efthimiou, Eleni (Frontiers in Communication, 2022)
Although signing avatar technology seems to be the only option currently available to serve sign language (SL) display in the context of applications which demand generative capacity from the part of the technology like in machine translation to SL, signing avatars have not yet been accepted by signers’ communities. One major factor for this rejection is the feeling that technology is developed without the involvement of its actual users. Aiming to invite the signers’ community into the process of signing avatar development, we have designed the shell methodological framework for signer-informed technology which is implemented as on-line surveys addressed to signer communities of different SLs. The surveys are communicated via focused on-line questionnaires with content of signing avatar performance that allows rating of various aspects of the produced SL synthetic signing by human signers. Here we report on the first survey application with content from the Greek Sign Language (GSL). The analysis of the obtained results is twofold: it highlights the significance of signer involvement and the provided feedback in the technological development of synthetic signing; in parallel it reveals those aspects of the survey setup that need fine-tuning before its next distribution cycles. The implementation of the first on-line survey can be found in: https://sign.ilsp.gr/slt-survey/.